Slit2 Protects Hearts Against Ischemia-Reperfusion Injury by Inhibiting Inflammatory Responses and Maintaining Myofilament Contractile Properties - Xiang Li; Shuang Zheng; Shuang Zheng; Weijiang Tan; Hongqi Chen; Xiaohui Li; Jian Wu; Ting Luo; Xuecong Ren; W. Glen Pyle; Lijing Wang; Peter H. Backx; et al. (Frontiers in Physiology, 2020)
BackgroundThe secreted glycoprotein Slit2, previously known as an axon guidance cue, has recently been found to protect tissues in pathological conditions; however, it is unknown whether Slit2 functions in cardiac ischemia–reperfusion (IR) injury.MethodsLangendorff-perfused isolated hearts from Slit2-overexpressing (Slit2-Tg) mice and C57BL/6J mice (background strain) were subjected to 20 min of global ischemia followed by 40 min of reperfusion. We compared Slit2-Tg with C57BL/6J mice in terms of left ventricular function and infarct size of post-IR hearts along with tissue histological and biochemical assessments (mRNA and protein expression, phosphorylation status, and myofilament contractile properties).ResultsSlit2 played cardioprotective roles in maintaining contractile function and reducing infarct size in post-IR hearts. IR increased the expression of the Slit2 receptor Robo4 and the membrane receptor Slamf7, but these increases were suppressed by Slit2 overexpression post IR. This suppression was associated with inhibition of the nuclear translocation of NFκB p65 and reductions in IL-1β and IL-18 release into perfusates. Furthermore, Slit2 overexpression attenuated the increases in myofilament-associated PKCs and phosphorylation of cTnI at Ser43 in the post-IR myocardium. The myofilament calcium sensitivity and actomyosin MgATPase activity were preserved in the post-IR Slit2 myocardium.ConclusionOur work demonstrates that Slit2 inhibits inflammatory responses and maintains myofilament contractile properties, thus contributing, at least in part, to the prevention of structural and functional damage during IR.